The Effect Of Deep Breathing And Hand Massage On The Pain Of Ca Mammae Patients - Wahyu Indah Setiawati; Anis Ardiyanti; Diffa Risqa Arisdiani (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Ca mammae refers to a breach in breast tissue, originating from both the epithelium of the ductus and the lobe, spreading through lymphatic vessels to other organs in the body and potentially resulting in metastases? Swelling of the breasts signals this process, causing pain that, if not addressed, could result in complications and discomfort. Deep breathing techniques and hand massage can alleviate the pain. The criteria of the patients with ca mammae are mild to moderate pain, and those with emergency conditions, shortness of breath, olive oil allergies, and injuries to hands and infusions. This quantitative quasi-experiment with a one-group pretest-posttest design used purposive sampling techniques on a sample of 45 people. This study uses a numerical assessment scale (NRS). The researchers analyze the data using the Wilcoxson test. The results showed a p-value of 0.000 for the majority of adults aged 46–65 (48.9%), PS education (44.4%), unemployment (82.2%), stage (62.2%), and treatment (53.3%). This study finds the effect on the ca mammae patient. When using more pure oils, additional research recommendations should be considered.